2019
DOI: 10.3390/polym11091384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Treatment on Crystallinity of Poly(ethylene oxide) Electrospun Fibers

Abstract: Post-process thermal treatment of electrospun fibers obtained from poly(ethylene oxide) (PEO) water and methanol solutions was examined. PEO fibers from methanol solution showed larger diameters as observed by scanning electron microscopy. Fibers both from water and methanol solutions exhibited a significant dimensional stability and surface cracking during the specific exposure time after thermal treatments at 40, 50, and 60 °C. Changes in crystallinity after the thermal treatment were studied by wide-angle X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…Such results may be attributed to the orientation of the macromolecular chains within the polymer in the longitudinal fibre direction under an electrostatic field during the electrospinning process, which may promote crystallisation. Such effect was also observed for other polymers [54][55][56][57]. Similarly, P(iPrOx-nPrOx) copolymers were amorphous before electrospinning, but a nonsymmetric peak (∆H~2.7 J/g) was visible in the DSC trace after its processing, indicating crystallisation.…”
Section: Discussionsupporting
confidence: 55%
“…Such results may be attributed to the orientation of the macromolecular chains within the polymer in the longitudinal fibre direction under an electrostatic field during the electrospinning process, which may promote crystallisation. Such effect was also observed for other polymers [54][55][56][57]. Similarly, P(iPrOx-nPrOx) copolymers were amorphous before electrospinning, but a nonsymmetric peak (∆H~2.7 J/g) was visible in the DSC trace after its processing, indicating crystallisation.…”
Section: Discussionsupporting
confidence: 55%
“…The ethanol treatment was applied to as-spun LDPE/PVB blend fibers at room temperature for 6 h. To remove PVB from closely associated LDPE, ethanol enters the core of the LDPE fiber and enhances the arrangement of polymer chains after the PVB matrix dissolves. Polaskova et al [43] also observed the improved molecular orientation and crystallinity of electrospun fiber with accompany of methanol solution. Like LDPE/PVB film, the crystallinity of PVB-removed LDPE fiber was improved by the increase of PVB content in blend fibers.…”
Section: Dsc Analysis Of Fibersmentioning
confidence: 89%
“…The crystallinity of LDPE was drastically decreased for electrospinning in blends with higher PVB content. Generally, the crystallinity of a polymer is a function of the supercooling [41,42] and is significantly lower for electrospun fibers compared to samples prepared by common processing technologies (molding or film casting) [43]. Here, M-ESP was conducted at room temperature, where the polymer was melted at around 200 °C by laser, and as-spun fibers were collected immediately by a collector.…”
Section: Structure Of Pvb-removed Ldpe Fibersmentioning
confidence: 99%
“…It is worth mentioning that the surface morphology and properties of electrospun fibers can be affected by (I) the working parameters of the electrospinning process represented by ambient parameters (relative humidity and temperature), solution parameters (polymer concentration, molecular weight, viscosity, conductivity, and surface tension), and processing parameters (flow rate, applied voltage, distance between the tip of the needle and the collector [DTC], collector type, and diameter of the needle); (II) electrospinning types; (III) composites; and (IV) postprocessing treatments …”
Section: Brief Introduction Of Electrospinningmentioning
confidence: 99%